What Firms Make vs. What They Know: How Firms' Production and Knowledge Boundaries Affect Competitive Advantage in the Face of Technological Change - Kapoor, Rahul; Adner, Ron (Organization Science, 2012)
Product innovation often hinges on technological changes in underlying components and architectures, requiring extensive coordination between upstream component development tasks and downstream product development tasks. We explore how differences in the ways in which firms are organized with respect to components affect their ability to manage technological change. We consider how firms are organized in terms of both division of labor and division of knowledge. We categorize product innovations according to whether they are enabled by changes in components or by changes in architectures. We test our predictions in the context of the global dynamic random access memory industry from 1974 to 2005, during which it transitioned through 12 distinct product generations. We find that vertically integrated firms had, on average, a faster time to market for new product generations than nonintegrated firms. The performance benefit that firms derived from vertical integration was greater when the new product generation was enabled by architectural change than when it was enabled by component change. We also find that although many nonintegrated firms extended their knowledge boundaries by developing knowledge of outsourced components, the performance benefits from such knowledge mostly accrued to “fully nonintegrated” firms (i.e., those that did not vertically integrate into any upstream component), rather than “partially integrated” firms (i.e., those that vertically integrated into some components but not others). Our study makes a strong case for the value of integrating the knowledge- and governance-based theoretical perspectives to broaden our examination of how firms organize for innovation and to uncover the technological and organizational sources of performance heterogeneity.